Pengaruh Return On Aset,Current Ratio Terhadap Debt To Equity Ratio Pada Perusahaan Plastik Dan Kemasan Yang Terdaftar di BEI - Shela Rahmatika Dewi; Anita Abdul Aziz (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of Return On Assets (ROA) and Current Ratio (CR) on Debt to Equity Ratio (DER) in plastic and packaging companies listed on the Indonesia Stock Exchange (BEI). The research method used is a quantitative method with a causal approach. The data used in this research is secondary data obtained from company financial reports published on the official IDX website during the 2020-2023 period. The research sample was selected using a purposive sampling technique, with a total of 5 companies that met the inclusion criteria. Data analysis was carried out through several stages, including descriptive analysis, classical assumption testing, and multiple linear regression analysis. The research results show that Return On Assets (ROA) has a negative and significant effect on the Debt to Equity Ratio (DER), while the Current Ratio (CR) does not have a significant effect on the Debt to Equity Ratio (DER). These findings indicate that companies with better asset management efficiency tend to have lower levels of debt compared to their equity.